Infants’ advances in speech perception shape their earliest links between language and cognition - Perszyk, Danielle R. (Sci Rep, 2019)
The power of human language derives not only from the precision of its signal or the complexity of its grammar, but also from its links to cognition. Infants as young as 3 months have begun to link language and core cognitive capacities. At 3 and 4 months, this link is not exclusive to human language: listening to vocalizations of nonhuman primates also supports infant cognition. By 6 months, infants have tuned this link to human speech alone. Here we provide evidence that infants’ increasing precision in speech perception shapes which signals they will link to cognition. Infants listening to German, a nonnative language that shares key rhythmic and prosodic properties with their own native language (English), successfully formed object categories. In contrast, those listening to Cantonese, a language that differs considerably in these suprasegmental properties, failed. This provides the first evidence that infants’ increasingly precise perceptual tuning to the sounds of their native language sets constraints on the range of human languages they will link to cognition: infants begin to specify which human languages they will link to core cognitive capacities even before they sever the link between nonhuman primate vocalizations and cognition.